Management of General Secondary Schools, According to the Concept of Total Quality from the Perspective of Teachers ''A Field Study in Public Secondary Schools of the City of Lattakia'' - Alali, Shiraz (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
The research aims to detect the possibility of secondary schools management in the city of Lattakia, according to total quality management from the perspective of teachers, And to know the differences in attitudes towards management of secondary schools, according to the concept of total quality depending on the following variables (sex, educational qualification, years of teaching experience). To achieve the objectives of the research, a questionnaire composed was designed including (72) items distributed to the seven areas (scholar strategic planning, the quality of teaching and learning processes, Educational Evaluation, openness to the community, educational leadership actors, organizational culture in the school, and information management at the school). The questionnaire was conducted on a sample of (278) teachers, with (18%) percentage for the academic year 2014-2015. Validity of the questionnaire was established though a jury of (7) of the teaching staff of educational at Damascus and Tishreen Universities and the Reliability was established by Cronbach – Alpha Reliability at lest (0.7). Results of answers sample of teachers showed that the of the degree of management of secondary schools in the city of Lattakia is medium according to the concept of total quality, and that the differences between the mean scores of the teachers' answers about secondary schools management were dependent on the variables of (sex and years of job experience) which is function and not substantial, while The results showed a substantial and significant differences depending on the scientific and educational qualification variable in favor of graduate campaign and made several recommendations, the most important research activation of TQM in public secondary schools management, and to disseminate the culture of quality among all employees.